How does Paylater Influence Consumer Purchase Behavior in Digital Markets? - Teguh Purwanto; Tutut Dwi Andayani; Moegiri Moegiri (Faculty of Economics and Business Universitas Jenderal Soedirman, 2025)
The phenomenon of online shopping via e-commerce platforms is currently a trend. The number of transactions continues to increase from year to year indicating a shift in shopping behavior patterns. This is supported by changes in consumer behavior in making purchases as a result of the Covid-19 pandemic. The various payment methods provided by e-commerce platforms are increasingly varied, including the increasing development of Financial Technology, including the Digital Accumulated Balance Payment System Pay Later. This study aims to investigate price, hedonic motivation, and promotion on buying intention. Then test the moderation role of the paylater feature. The element of novelty produced in this research is the difference in consumer perceptions of paylater features regarding conventional and sharia. Quantitative research, data was obtained using purposive random sampling, processed using PLS-SEM with a total of 130 e-commerce user respondents. The results of this research show that price and promotion have a positive and significant effect on buying interest, hedonic motivation has no effect on buying interest, and paylater features do not moderate it. Future research can classify target respondents based on their views and preferences, such as conventional and sharia